The optimum condition for the synthesis of carbon nanofibers on activated carbon to remove lead from aqueous solution - Mamun, Abdullah Al; Ahmed, Yehya M.; Al-Khatib, Ma'an Fahmi Rashid; Jameel, Ahmad T.; Al Saadi, Mohammed A. (Penerbit UniMAP (UniMAP PRESS), 2019)
Optimum process condition for the production of Carbon Nanofibers (CNFs) to remove lead ion (Pb) from aqueous solution is reported here. The CNFs were produced on the catalyst (Ni2+) impregnated palm oil-based cheap Powder Activated Carbon (PAC). Locally fabricated Chemical Vapour Deposition (CVD) system was used while acetylene (C2H2) was the carbon source. The porous nano-composite product is named “PAC-CNFs”, which was synthesized through a process using impregnated oil palm shell based PAC as a solid substrate. Design Expert 6.0.8 software was used to design the experimental plan and to determine the optimized process parameters for the growth of CNFs by using sorption capacity for Pb2+ by the PAC-CNFs adsorbent, as a response. The effect of different factors on the growth of CNFs including the temperature of CNFs growth (550 to 750 °C), time of growth (30 to 60 min), and the ratio of input C2H2/H2 gases (0.25 to 1.0) was evaluated. The predicted values for the sorption capacity of Pb2+ by the PAC-CNFs were in close agreement with the experimental data (R2 = 0.99). The optimal process condition: temperature for the growth of CNFs, time, and C2H2/H2 ratio was determined as 637 °C, 30 min, and 1.0, respectively. The CNFs grown under the optimized condition exhibited sorption capacity of 77 mg/g in removing Pb2+ from synthetic wastewater containing lead (Pb2+) ion.